Mit Sozialpolitik regieren Eine ressourcentheoretische Policy-Analyse der Beschäftigungsförderung benachteiligter Jugendlicher in Österreich - Knecht, Alban (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2024)
How can labor market policy best help young people enter the workforce? This in-depth analysis of employment support for disadvantaged youth in Austria discusses the introduction of measures such as the supra-company apprenticeship, the training guarantee and compulsory training against the background of their political discussion and their socio-political implementation. The research findings obtained are not only relevant for Austria, but also offer valuable insights for training systems worldwide.